2011
DOI: 10.1002/eji.201141648
|View full text |Cite
|
Sign up to set email alerts
|

Human β‐defensin 3 affects the activity of pro‐inflammatory pathways associated with MyD88 and TRIF

Abstract: β-Defensins are cationic host defense peptides that form an amphipathic structure stabilized by three intramolecular disulfide bonds. They are key players in innate and adaptive immunity and have recently been shown to limit the production of pro-inflammatory cytokines in TLR4-stimulated macrophages. In the present study, we investigate the mechanism underlying the anti-inflammatory effect of human β-defensin 3 (hBD3). We show that the canonical structure of hBD3 is required for this immunosuppressive effect a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
109
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 128 publications
(117 citation statements)
references
References 42 publications
4
109
2
Order By: Relevance
“…However, findings in knockout mice (matrilysin deficient) suggested that direct pathogen clearance was at least one mechanism of defensin function (25). Second, antimicrobial peptides, including hBD3, have been shown to demonstrate a biphasic effect, being proinflammatory at higher concentrations, but anti-inflammatory at lower levels (23,26,27). In contrast, our data showed hBD3 did not increase the expression of TNF-α in enterocytes.…”
Section: Discussioncontrasting
confidence: 69%
“…However, findings in knockout mice (matrilysin deficient) suggested that direct pathogen clearance was at least one mechanism of defensin function (25). Second, antimicrobial peptides, including hBD3, have been shown to demonstrate a biphasic effect, being proinflammatory at higher concentrations, but anti-inflammatory at lower levels (23,26,27). In contrast, our data showed hBD3 did not increase the expression of TNF-α in enterocytes.…”
Section: Discussioncontrasting
confidence: 69%
“…32 In previous studies, proinflammatory cytokines, such as TNF-α and IL-6, were completely blocked by hBD3 in pathogen-induced macrophages isolated from human bone marrow both in vitro and in vivo 33 through toll-like receptor-mediated signaling pathways and the subsequent transcriptional inhibition of inflammatory genes. 34 However, the therapeutic application of hBD3 has some limitations, including the difficulty of mass production due to its long amino acid sequence and the decreased stability observed at high ionic strength. Importantly, three disulfide bonds containing six cysteines maintain the stability of the hBD3 structure, as well as its anti-inflammatory properties.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to LPS binding, the direct interference of DEFB114 in inflammation signaling pathways in the presence of LPS could not be excluded. Among human DEFBs, DEFB103 associates with and rapidly enters macrophages and then inhibits both MyD88 and TRIF signaling pathways, resulting in the transcriptional repression of proinflammatory genes (38). Whether DEFB103 and DEFB114 utilize a similar mechanism to exert their anti-inflammatory activity is an interesting question.…”
Section: Discussionmentioning
confidence: 99%